1998
DOI: 10.1161/01.cir.97.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Insight Into the Possible Optimal Therapies for Acute Myocardial Infarction and Unstable Angina

Abstract: T he optimal treatment of unstable ischemic coronary syndromes has not been settled, and little in vivo pathological information in humans has been available to help guide the care of patients with these complicated problems. Dr Van Belle and colleagues 1 have given us new insight into the underlying pathophysiological substrate in patients sustaining acute myocardial infarction who then underwent coronary angioscopy before coronary interventions up to 1 month after their index event. Of these patients, 98% we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…There were significant (PϽ.05) positive correlations between severity of the unstable angina presentation and presence of an intracoronary thrombus or complex lesion. Results of angioscopic studies 24 also indicate that intracoronary thrombus or yellow plaque is found in most unstable culprit arteries but infrequently in stable angina. The thrombus in unstable angina has been characterized as grayish-white and presumably platelet-rich, whereas in MI it was red.…”
Section: Thrombus Formation In Unstable Anginamentioning
confidence: 98%
“…There were significant (PϽ.05) positive correlations between severity of the unstable angina presentation and presence of an intracoronary thrombus or complex lesion. Results of angioscopic studies 24 also indicate that intracoronary thrombus or yellow plaque is found in most unstable culprit arteries but infrequently in stable angina. The thrombus in unstable angina has been characterized as grayish-white and presumably platelet-rich, whereas in MI it was red.…”
Section: Thrombus Formation In Unstable Anginamentioning
confidence: 98%